Contribution of insect gut microbiota and their associated enzymes in insect physiology and biodegradation of pesticides - Jaffar, Saleem; Ahmad, Sajjad; Lu, Yongyue (Frontiers in Microbiology, 2022)
Synthetic pesticides are extensively and injudiciously applied to control agriculture and household pests worldwide. Due to their high use, their toxic residues have enormously increased in the agroecosystem in the past several years. They have caused many severe threats to non-target organisms, including humans. Therefore, to protect the ecosystem and the diversity of living organisms, the complete removal of toxic compounds is gaining wide attention. Several methods, such as physical, chemical and biological, are applied to degrade compounds, but as compared to other methods, biological methods are considered more efficient, fast, eco-friendly and less expensive. In particular, the employment of microbial species and their purified enzymes makes the degradation of toxic pollutants more accessible and converts them into non-toxic products by several metabolic pathways. The digestive tract of insects is usually known as a superior organ that provides a nutrient-rich environment to hundreds of microbial species that perform a pivotal role in various physiological and ecological functions. There is a direct relationship between pesticides and insect pests: pesticides reduce the growth of insect species and alter the phyla located in the gut microbiome. In comparison, the insect gut microbiota tries to degrade toxic compounds by changing their toxicity, increasing the production and regulation of a diverse range of enzymes. These enzymes breakdown into their derivatives, and microbial species utilize them as a sole source of carbon, sulfur and energy. The resistance of agrochemicals in insect species is developed by metabolic mechanisms, regulation of enzymes and the expression of various microbial detoxifying genes in insect guts. This review summarizes the toxic effects of agrochemicals on humans, animals, birds and beneficial arthropods. It explores the preferential role of insect gut microbial species in the degradation process and the resistance mechanism of several pesticides in insect species. Additionally, various metabolic pathways have been systematically discussed to better understand the degradation of xenobiotics by insect gut microbial species.